Methicillin-resistant Staphylococcus aureus Swab Results Did Not Change Treatment or Outcome in Pediatric Spinal Fusion Patients. Issue 17 (1st September 2018) - Nielsen, Ena; Andras, Lindsay M.; Harris, Liam R.; Skaggs, David L.
Abstract : Introduction: The aim of this study was to investigate whether preoperative methicillin-resistant Staphylococcus aureus (MRSA) swab results were predictive of surgical site infections (SSIs) in pediatric patients who have undergone spinal fusion. Methods: We conducted a retrospective chart review of patients who underwent posterior spinal fusion between 2004 and 2014 to determine preoperative MRSA colonization status and SSI rates and organisms. Before October 1, 2012, we administered vancomycin to the patients for infection prophylaxis; beginning October 1, 2012, patients received ceftazidime and Ancef (cefazolin for injection; GlaxoSmithKline). We added powdered vancomycin to all bone grafts. Results: A total of 1, 200 patients met inclusion criteria. Of the patients, 2.3% (n = 28 of 1, 200) were positive for MRSA, and an SSI developed in 3.1% (n = 37 of 1, 200). No significant difference in infection rates was found between patients whose MRSA swab was positive and negative (positive swab = 1 SSI, negative swab = 36 SSIs; P = 0.88). Three SSIs were caused by MRSA. Conclusion: The results of a preoperative MRSA nasal swab had no correlation with SSI rates. Level of Evidence: Level III